Analisis Kinerja Perusahaan Asuransi Umum Nasional dan Perusahaan Asuransi Umum Patungan di Indonesia - Yohanes Jhony Kurniawan; Heppy Julianto; Suhartono Suhartono (CV. Ulil Albab Corp, 2024)
This analysis reflects the performance of National General Insurance Companies and Joint Venture General Insurance Companies in Indonesia. This allows this mapping to be used as a tool to analyze and control the performance of National General Insurance Companies and Joint Venture General Insurance Companies in Indonesia. So based on the above we will raise the research title